INTERAKSI SOSIAL DALAM RITUAL ADAT DAN GOTONG ROYONG PROSES BERLADANG SUKU DAYAK TAMAMBALO APALIN DESA SUNGAI ULUK PALIN - Sinta, Septiana Clara; Basri, Muhammad; Kuswanti, Heni (Universitas Tanjungpura, 2025)
This research examines social interactions in customary rituals and community cooperation in the farming process of the Dayak Tamambalo Apalin tribe in Sungai Uluk Palin Village. A qualitative approach was used with a case study method to explore how local cultural values influence social interactions and economic sustainability in their farming practices. This study involves the collection of data through participatory observation, in-depth interviews, and related document analysis. The research results show that the traditional ritual, Pamolek Beok, is a form of celebration that is held to conclude the entire series of farming processes. Gotong royong, in the form of mutual assistance in working the fields and sharing harvests, not only optimizes resources but also strengthens social relationships among community members. The social interaction that occurs in this farming practice not only involves economic dimensions but also spiritual and ecological values. The active involvement of all community members demonstrates a collective commitment to environmental preservation as well as sustainable local economic development. This process illustrates how traditional practices can adapt to advancements in modern technology without sacrificing a rich cultural heritage. This research emphasizes the importance of understanding and promoting culturally-based farming practices as a model for strengthening communities, enhancing economic well-being, and maintaining environmental balance. This research can assist the Dayak Tamambalo Apalin community and similar communities worldwide by promoting the preservation of culture and the environment as well as providing insights for sustainable development policies.